Possibilities of innovative development of the company in business model construction - M. A. Yakhjyaev; B. R. Shakirtkhanov (Путеводитель предпринимателя, 2020)
Innovations are connected about uncertainty and risk as the effect from their introduction has, as a rule, long-term character and is connected with bigfinancial expenses. However process of improvement forces the companies to develop around the world achieving the global objectives and solving complex problems in creation of own business model.